Management of pterygium surgery: Limbal Conjunctival Autograft and Subconjunctival Amniotic Membrane Graft - Reisyah Syahfira; Putu Ristyaning Ayu Sangging; Rani Himayani (Medula, 2023)
Pterygium is one of the common ocular surface disorders. From two Greek words, the word "pterygium" has been derived: “pteryx” meaning wing and “pterygion” meaning fin. Usually, pterygium is asymptomatic apart from its appearance. Meanwhile, no special examination is needed to diagnose it, only a physical examination is needed using a slit lamp to diagnose this condition. A slit lamp for observing the eye using magnification and bright lighting. Medical treatment in modern times includes lubrication with artificial tear drops or decongestants to provide short-term comfort and a slight improvement in cosmetics. Topical NSAIDs, eye drop loteprednol, brings added comfort. Vasoconstrictive agents minimize redness and enhance the appearance and add antihistamines to the decongestant drops to help prevent the effect of histamine associated edema and itching. However, surgical treatment remains the preferred option. In patients with pterygium, the reasons for surgery are decreased vision due to visual axis encroachment, chronic pain, persistent inflammation, abnormal astigmatism, restrictive ocular motility, and cosmesis. Many surgical techniques have been used since past to present, though none is universally accepted because of variable recurrence rates. Some examples of surgery, namely the avulsion technique, Simple excision technique, The Bare Sclera Technique, Conjunctival Autograft, and Limbal Conjunctival Autotransplant (LCAT). However, combined between limbal conjunctival autograft with the adjunctive use of a prophylactic subconjunctival graft of the amniotic membrane can decrease the recurrence rate after surgery in an ethnically diverse population with a statistically higher risk for recurrence.